Small scale experiments of sloshing considering the seismic safety of MYRRHA. (11th May 2016) - Myrillas, Konstantinos; Planquart, Philippe; Buchlin, Jean-Marie; Schyns, Marc
Abstract: Sloshing can be a great concern for the seismic safety of heavy liquid metal cooled nuclear reactors, such as the Gen IV prototype MYRRHA, currently under development by the Belgian Nuclear Research Center (SCKCEN). Sloshing is studied using reduced scale laboratory experiments on the SHAKESPEARE shaking table facility of the von Karman Institute. Scaling of the experimental model is discussed through dimensional analysis, identifying the appropriate scaling factors which are then applied to the seismic excitation signals. Qualitative results of the liquid sloshing motions inside the model are obtained with flow visualization, while moments are measured on an instrumented rod that is partially immersed in the liquid. A two component moment-balance is constructed to measure the bending moments on the element about the horizontal axes. The results demonstrate that sloshing, as a non-linear phenomenon, is highly dependent on the frequency of forcing relative to the natural frequency of the liquid in the specific container. In the resonance case the sloshing response reaches the highest amplitude and maximum moments are measured, representing a worst case scenario for the reactor safety. Experiments with internal components in the sloshing model indicate that obstructions reduce the sloshing loads and prevent resonance type sloshing. The proposed methodology with small scale experiments can provide a useful tool for the prediction of the sloshing effects for the MYRRHA design and safety analysis. Highlights: Sloshing is studied for the MYRRHA Gen IV nuclear reactor using LBE for cooling. Small scale experiments of sloshing are conducted on a shaking table facility. Scaling rules for the reduced scale experimental model are suggested. Moments are measured on a cylindrical immersed element using a moment-balance. Flow visualization is shown for the model reactor with and without internals.